2021
DOI: 10.3390/molecules26030564
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity on Human Colon Adenocarcinoma Cells and In Vitro Antioxidant Effect of Anthocyanin-Rich Extracts from Peels of Species of the Myrtaceae Family

Abstract: There is a significant indication of the beneficial health effects of fruit rich diets. Fruits of native plant species have noticeably different phytochemicals and bioactive effects. The aim of this work was to characterize and compare the constituents of jabuticaba (Myrciaria jaboticaba, MJ), jamun-berry (Syzygium cumini, SC), and malay-apple (Syzygium malaccense, SM) extracts and their influence on antioxidant activity in vitro and antiproliferative effects on human colon adenocarcinoma cells. According to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Similar effects were verified using coloured phenolics from pollen, but at a higher concentration (10 mg/mL) [ 175 ]. Concentrations higher than 500 µg/mL of anthocyanin-rich extracts from the Myrtaceae family also showed an ability to reduce the proliferation of human colon adenocarcinoma HT-29 cells, mainly by arresting the G2/M phase, hence causing cell apoptosis in comparison with the control group over 24 h of treatment [ 176 ]. It was also already verified that anthocyanin-rich extracts from pomegranate at 50 µg/mL can reduce by 10% the growth of human bladder cancer T24 cells growth after 48 h of exposure, in comparison with untreated cells [ 170 ].…”
Section: Putative Health Benefitsmentioning
confidence: 99%
“…Similar effects were verified using coloured phenolics from pollen, but at a higher concentration (10 mg/mL) [ 175 ]. Concentrations higher than 500 µg/mL of anthocyanin-rich extracts from the Myrtaceae family also showed an ability to reduce the proliferation of human colon adenocarcinoma HT-29 cells, mainly by arresting the G2/M phase, hence causing cell apoptosis in comparison with the control group over 24 h of treatment [ 176 ]. It was also already verified that anthocyanin-rich extracts from pomegranate at 50 µg/mL can reduce by 10% the growth of human bladder cancer T24 cells growth after 48 h of exposure, in comparison with untreated cells [ 170 ].…”
Section: Putative Health Benefitsmentioning
confidence: 99%
“…The biological implication of the gut-derived PC metabolites of JPP remains unknown as previous studies on JPP fermentation were limited to the description of PC transformation during simulated digestion [ 12 ]. Although the antiproliferative effect of JPP extract in HT29 monolayer cells has been recently reported [ 13 ], no studies were found regarding the antiproliferative effects in CRC 3D cell models or the effects of colonic fermented JPP (FJPP).…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins could have both chemopreventive and therapeutic effects against various types of cancer. In this Special Issue, four papers explored the anthocyanins’ anti-cancer effects [ 5 , 6 , 7 , 8 ]. Two of those papers report the results of in vitro studies carried out, by the same research group, to evaluate the anticancer effects of Vitis coignetiae Pulliat [ 5 , 6 ].…”
mentioning
confidence: 99%
“…This result highlights the need for further research to validate the anti-cancer effects of anthocyanins in highly metastatic cancer or far advanced cancers characterized by high TNF-α levels [ 7 ]. Simas Frauches et al [ 8 ] carried out a study which aimed to characterize and compare the constituents of jabuticaba ( Myrciaria jaboticaba ), Jamun berry ( Syzygium cumini ), and Malay apple ( Syzygium malaccense ) extracts and their effect on antioxidant activity in vitro and antiproliferative effects on human colon adenocarcinoma cells. The results, published in this Special Issue, show a decrease in cell viability of HT-29 cells after treatment with Myrtaceae fruits extracts.…”
mentioning
confidence: 99%
See 1 more Smart Citation